Student-Athletes with Learning Disabilities: Unique Problems, Unique Solutions - Lane, Holly B.; Blatz, Sharon L.; Ziegert, Cheryl C.; Jordan, LuAnn; Allsopp, David H.; Moriarty, Tamara A.; Dede, Duane E.; Conway, Tim W. (My University, 2001)
This paper explored the issues/acing student-athletes with learning disabilities and their academic counselors. Understanding the nature of learning disabilities and their effects can enhance the counselor's ability to address the complex needs of the student-athlete with a learning disability. The increasing numbers of college student-athletes who have diagnosed learning disabilities demands notice. This paper provided an explanation of the problems of diagnosis and treatment. Suggestions for academic counselors were provided, as well.
Keywords: at-risk